2005
DOI: 10.1021/cm0518325
|View full text |Cite
|
Sign up to set email alerts
|

Sol−Gel Processing of Semiconducting Metal Chalcogenide Xerogels:  Influence of Dimensionality on Quantum Confinement Effects in a Nanoparticle Network

Abstract: The synthesis and characterization of porous nanostructured inorganic polymers (gels and xerogels) of CdS, ZnS, PbS, and CdSe is described. Primary particles are synthesized via water-in-oil microemulsions, surface complexed with thiolate ligands, and dispersed in acetone. Oxidation of the thiolate ligands with H 2 O 2 leads to particle aggregation and the formation of wet gels, which are then dried under ambient conditions to produce xerogels. The xerogels exhibit optical band-edges that are intermediate betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 54 publications
5
70
0
2
Order By: Relevance
“…The optical data are summarized in Table 1. The observed energy values, when compared to the bulk value of 0.28 eV, are all blue‐shifted, suggestive of quantum confinement effects in the dried gels prepared from PbSe nanospheres 1719. The xerogel is significantly red‐shifted from the aerogel, consistent with the effect of density on quantum confinement effects noted for other metal chalcogenide gel systems 18,41.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…The optical data are summarized in Table 1. The observed energy values, when compared to the bulk value of 0.28 eV, are all blue‐shifted, suggestive of quantum confinement effects in the dried gels prepared from PbSe nanospheres 1719. The xerogel is significantly red‐shifted from the aerogel, consistent with the effect of density on quantum confinement effects noted for other metal chalcogenide gel systems 18,41.…”
Section: Resultssupporting
confidence: 63%
“…In 2004, we reported a method for preparation of aerogels of CdS by oxidation‐induced assembly of thiolate‐capped CdS particles to produce a gel, followed by supercritical drying. In 2005, we demonstrated the applicability of this method to PbS, ZnS, and CdSe as well and showed that the quantum confinement effects observed in both the aerogels and the more dense xerogels (ambient pressure dried gels) are due to the low dimensionality of the network, rather than from any barriers between the particles 1719. Specifically, it was found that the extent of quantum confinement effects in gels correlates with the surface area and porosity of the gels.…”
Section: Introductionmentioning
confidence: 91%
“…[29,52,53] Furthermore they showed that the surface of the particles is still exposed and can be modified even after the assembly.Inalater study this feature was used to extend the possible aerogel materials to PbSe and CuSe through ac ation-exchange reaction in the pre-formed CdSe gels. [29,52,53] Furthermore they showed that the surface of the particles is still exposed and can be modified even after the assembly.Inalater study this feature was used to extend the possible aerogel materials to PbSe and CuSe through ac ation-exchange reaction in the pre-formed CdSe gels.…”
Section: Quantum-confined Macroscopic Solidsmentioning
confidence: 99%
“…[29,52,53] Des Weiteren zeigten sie,d ass die Partikeloberfläche noch immer zugänglich ist und sogar nach der Anordnung modifiziert werden kann. [29,52,53] Des Weiteren zeigten sie,d ass die Partikeloberfläche noch immer zugänglich ist und sogar nach der Anordnung modifiziert werden kann.…”
Section: Quantenbeschränkte Makroskopische Feststoffeunclassified